A numerical investigation into the strength of offshore jacket platforms considering time-variant zonal corrosion subjected to alternative ship impacts - Reza Zendehdel; Mohammad Reza Khedmati (Heliyon)
In addition to the usual loads, fixed jacket offshore platforms can be exposed to accidental loads from ship collisions. Indentation of tubular components is a significant defect that occurs when a supply vessel collides with a jacket platform, which can affect the ultimate strength of the offshore platform. This paper performs a nonlinear dynamic analysis using ABAQUS software to evaluate the ultimate strength of a wellhead jacket platform and to investigate its structural response to two consecutive impacts from a 2700-ton ship. A total of 16 collision scenarios were simulated and analyzed. The research incorporates time-varying zonal corrosion for jacket platforms, as discussed by Yang et al., and employs beam and shell elements for the numerical modeling of the jacket platform, using a rigid model for the offshore supply vessel. The results indicate that the key factors affecting structural damage are the corrosion rate, consecutive impacts, and the shape of the impacting structure. Findings reveal that local indentation and local displacement are directly proportional to increases in the corrosion rate. However, the bending deformation parameter shows a different pattern: it has an inverse relationship with the corrosion rate and a direct relationship with the number of collisions. In sideway and stern collisions, the primary impact in each corrosion scenario has almost the same effect on the ultimate strength of the structure as the secondary impact in the previous corrosion scenario. However, in forecastle impacts, the effect of the secondary impact is greater than that of the primary impact in the subsequent corrosion scenario, equivalent to a 10-year increase in corrosion.